2003
DOI: 10.1128/mcb.23.20.7096-7107.2003
|View full text |Cite
|
Sign up to set email alerts
|

14-3-3σ Positively Regulates p53 and Suppresses Tumor Growth

Abstract: The 14-3-3 (sigma) protein, a negative regulator of the cell cycle, is a human mammary epithelium-specific marker that is downregulated in transformed mammary carcinoma cells. It has also been identified as a p53-inducible gene product involved in cell cycle checkpoint control after DNA damage. Although 14-3-3 is linked to p53-regulated cell cycle checkpoint control, detailed mechanisms of how cell cycle regulation occurs remain unclear. Decreased expression of 14-3-3 was recently reported in several types of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
227
0
5

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 220 publications
(261 citation statements)
references
References 46 publications
23
227
0
5
Order By: Relevance
“…As expected, our domain-binding assays indicate that 14-3-3s employs the C-terminal domain to interact with the C-terminal domains of MDM2 or p53 (Figure 2). Hence, on the basis of these results, we have proposed a working model (Figure 7) that incorporates and extends previous findings that 14-3-3s is a positive regulator of p53 (Yang et al, 2003). As presented in the model, when 14-3-3s is not induced in unstressed cells (Figure 7a), 14-3-3s may use its C-terminal domain to interact with C-terminal domains of MDM2 or p53, while MDM2 and p53 are still interacting with each other through respective Nterminal domain.…”
Section: Discussionsupporting
confidence: 71%
See 4 more Smart Citations
“…As expected, our domain-binding assays indicate that 14-3-3s employs the C-terminal domain to interact with the C-terminal domains of MDM2 or p53 (Figure 2). Hence, on the basis of these results, we have proposed a working model (Figure 7) that incorporates and extends previous findings that 14-3-3s is a positive regulator of p53 (Yang et al, 2003). As presented in the model, when 14-3-3s is not induced in unstressed cells (Figure 7a), 14-3-3s may use its C-terminal domain to interact with C-terminal domains of MDM2 or p53, while MDM2 and p53 are still interacting with each other through respective Nterminal domain.…”
Section: Discussionsupporting
confidence: 71%
“…Indeed, a strategy to activate p53 in tumor by inhibiting MDM2 activity has been the focus in cancer drug discovery. We previously showed that 14-3-3s inhibits MDM2-mediated p53 ubiquitination (Yang et al, 2003). Thus, 14-3-3s is a potential negative regulator of MDM2.…”
Section: Introductionmentioning
confidence: 92%
See 3 more Smart Citations